Gypsum Precipitating From Volcanic Effluent as an Archive of Volcanic Activity - van Hinsberg, Vincent J.; Berlo, Kim; Pinti, Daniele L.; Ghaleb, Bassam (Frontiers in Earth Science, 2021)
Records of volcanic activity are a key resource in volcano monitoring and hazard mitigation. The time period for which such records are available and the level of detail vary widely among volcanic centers and there is, therefore, a need for supplementary sources of this information. Here, we use growth-zoned gypsum as a mineral archive of the activity of Kawah Ijen volcano in East-Java, Indonesia. Gypsum precipitates where water seeps from the crater lake and hydrothermal system, and it has formed a 100 m long cascading plateau. A 19 cm plateau cross-section was analysed for minor and trace elements using laser-ablation ICP-MS. Absolute ages were assigned to this transect based on 210Pb dating. This 210Pb age model was corrected for variations in the 210Pb0 resulting from fluctuations in the volcanic radon flux by using 84Kr/36Ar and 132Xe/36Ar. The age model indicates that the transect covers a period from 1919 ± 12 to 2008 ± 0.2. Gypsum-fluid partition coefficients (D) permit the gypsum compositions to be converted to the concentrations in the fluid from which each growth zone grew. The D-values also show the compatibility of the elements in the gypsum structure, and identify the LREE, Sr, Pb, Tl, Ni, Co, Cu, Zn, Cd, Sb, Th and Mo as least susceptible to contamination from rock fragment and mineral inclusions, and therefore as most reliable elements of the gypsum record. Compositional variability in the timeseries correlates with known element behavior in the Kawah Ijen system and shows three element groups: the LREE, Sr and Pb that represent rock-leaching; Cu, Zn, and Cd, which have previously been linked to immiscible sulfide destabilization in a deep-seated basalt; and Sb, Tl and As which point to a contribution from the shallow system and evolved magma. Moreover, the gypsum record shows that episodes of unrest and quiescence have a distinct compositional signature in Kawah Ijen seepage fluids, and can be distinguished. Thus, we show that gypsum is a sensitive recorder of volcanic activity and can provide detailed information on the state of the magmatic-hydrothermal system in the past.